The settlement of Yauna, 'Ionian' identity and the Greek presence on the Syrian coast in the second half of the eighth century BC: a reassessment of two letters from the Nimrud correspondence. (November 2022) - Radner, Karen; Vacek, Alexander
Abstract: We offer a reassessment of two letters from the state correspondence of Tiglath-pileser III of Assyria (r. 744–727 BC) with the earliest references to a town called Yauna and a people called the Yauneans, as encountered on the eastern Mediterranean coast by the newly established imperial administration. Past scholarship connected these Assyrian terms with the ethnonym 'Ionians' and/or the toponym 'Ionia'. The study narrows down the location of Yauna, drawing also on a review of the coastal sites that have produced Greek ceramic imports: although identification remains elusive, Yauna was certainly situated in the territory of the kingdom of Hamath, and later the Assyrian province of Ṣimirra. Discussion of the historical and cultural background of Yauna's foundation highlights its significance for the 'transfer debate' and the phenomenon of the 'Greeks overseas'. We argue that the Assyrians first encountered the Yauneans in this locality and that, to them, they were originally simply the inhabitants of Yauna. Due to the similarities perceived between them and (other?) Greeks appearing in the eastern Mediterranean, the Assyrians came to apply the ethnonym universally to all these people, who eventually adopted it for themselves. Thus, we support the argument that the term 'Ionian' originated in external nomenclature.